Research advances on encapsulation of probiotics with nanomaterials and their repair mechanisms on intestinal barriers - Xiaochen Wang; Mengxi Yu; Jianming Ye; Ting Liu; Lijuan Jian; Xiaoyan Zheng; Yuan Wang; Wei Song; Yane Luo; Tianli Yue (Food Science and Human Wellness)
Probiotics participate in various physiological activities and contribute to body health. However, their viability and bioefficacy are adversely affected by gastrointestinal harsh conditions, such as gastric acid, bile salts and various enzymes. Fortunately, encapsulation based on various nanomaterials shows tremendous potential to protect probiotics. In this review, we introduced some novel encapsulation technologies involving nanomaterials in view of predesigned stability and viability, selective adhesion, smart release and colonization, and efficacy exertion of encapsulated probiotics. Furthermore, the interactions between encapsulated probiotics and the gastrointestinal tract were summarized and analyzed, with highlighting the regulatory mechanisms of encapsulated probiotics on intestinal mechanical barrier, chemical barrier, biological barrier and immune barrier. This review would benefit the food and pharmaceutical industries in preparation and utilization of multifunctional encapsulated probiotics.